2009
DOI: 10.1109/tnet.2008.926505
|View full text |Cite
|
Sign up to set email alerts
|

Robust Synchronization of Absolute and Difference Clocks Over Networks

Abstract: We present a detailed re-examination of the problem of inexpensive yet accurate clock synchronization for networked devices. Based on an empirically validated, parsimonious abstraction of the CPU oscillator as a timing source, accessible via the TSC register in popular PC architectures, we build on the key observation that the measurement of time differences, and absolute time, requires separate clocks, both at a conceptual level and practically, with distinct algorithmic, robustness, and accuracy characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 14 publications
2
59
0
Order By: Relevance
“…Second, we found the main sources of this inaccuracy come from propagation delay asymmetry and queueing delay asymmetry in the wide area. Third, although the path delay asymmetry is considered not measurable [6] 1 , we find that synchronization accuracy is well-correlated with some path properties that can be probed by end-hosts. To address this, we evaluate several heuristics that compensate for this error (by estimating the error and correcting for it).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Second, we found the main sources of this inaccuracy come from propagation delay asymmetry and queueing delay asymmetry in the wide area. Third, although the path delay asymmetry is considered not measurable [6] 1 , we find that synchronization accuracy is well-correlated with some path properties that can be probed by end-hosts. To address this, we evaluate several heuristics that compensate for this error (by estimating the error and correcting for it).…”
Section: Introductionmentioning
confidence: 86%
“…Recently, novel frameworks [5,6] are proposed to further improve the synchronization accuracy. While these studies showed that some NTP servers are inaccurate, the underlying cause of inaccuracies remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For more general use however, where time intervals may be larger, the error may be unacceptable. In future work we will significantly reduce it by using timestamp in conjunction with the RADclock difference clock [2], [8].…”
Section: Timestamping Methodologymentioning
confidence: 99%
“…More importantly still, the fact that it does not respect causality (packets can, and often do, leave before their timestamp is made), means it cannot even be used to measure RTTs, and fatally, cannot be bounded by them. This is very dangerous for timekeeping as it excludes effective methods for the filtering of delay variability [2]. An alternative approach could be to pair an so timestamp on incoming with a different timestamp on outgoing.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation